Interpersonal violence against women and maternity care in Migori County, Kenya: evidence from a cross-sectional survey - Schellhammer, Sophie K.; Starnes, Joseph R.; Mudhune, Sandra; Goore, Lou; Marlar, Lauren; Oyugi, Samuel; Wamae, Jane; Shumba, Constance S.; Rogers, Ash; Mbeya, Julius; Vill, Beffy; Otieno, Angeline S.; et al. (Frontiers in Global Women's Health, 2024)
Background Interpersonal violence (IPV) is an issue of major public health concern, with 24% of Kenyan women reporting physical violence perpetrated by a current husband or partner. IPV has profound impacts on physical and mental health outcomes, particularly for pregnant women; it has been found to increase the risk of perinatal mortality, low birth weight, and preterm birth. This study aims to identify variables associated with IPV and assess the effects of IPV experience on prenatal and peripartum maternal healthcare in Migori County, Kenya. Findings build on a previous study that investigated a smaller region of Migori County. Methods Responses to cross-sectional household surveys conducted in six wards of Migori County, Kenya in 2021 from female respondents aged 18 and older were analyzed. The survey contained validated screening tools for interpersonal violence. Group-wise comparisons, and bivariate and multivariate logistic regression analyses were performed to describe community prevalence, factors associated with IPV against women, and the effect of IPV exposure on prenatal and peripartum health care. Results This study finds that 2,306 (36.7%) of the 6,290 respondents had experienced lifetime IPV. IPV experience was associated with the age group 25–49 (adjusted odds ratio (aOR) 1.208; 95%CI: [1.045–1.397]; p = 0.011), monogamous marriage [aOR 2.152; 95%CI: (1.426–3.248); p < 0.001], polygamous marriage [aOR 2.924; 95%CI: (1.826–4.683); p < 0.001], being widowed/divorced/separated [aOR 1.745; 95%CI: (1.094–2.786); p < 0.001], feeling an attitude of “sometimes okay” toward wife beating [aOR 2.002 95%CI: (1.651, 2.428); p < 0.001], having been exposed to IPV in girlhood [aOR 2.525; 95%CI: (2.202–2.896); p < 0.001] and feeling safe in the current relationship [aOR 0.722; 95%CI: (0.609, 0.855); p < 0.001]. A depression score of mild [aOR 1.482; 95%CI: (1.269, 1.73); p < 0.001] and severe [aOR 2.403; 95%CI: (1.429, 4.039); p = 0.001] was also associated with IPV experience, and women who experienced emotional abuse were much more likely to have experienced IPV [aOR 10.462; 95% CI: (9.037, 12.112); p < 0.001]. Adjusted analyses showed that having experienced IPV was negatively associated with attending at least four antenatal care visits during the most recent pregnancy (OR 0.849, p = 0.044) and with having a skilled birth attendant (OR 0.638, p = 0.007). Conclusions IPV is prevalent in Migori County, Kenya, with increased prevalence among women aged 25–49, those residing in West Kanyamkago, those in a monogamous or polygamous marriage, those who have been widowed/divorced/separated, and those with severe depressive symptoms. Further, IPV exposure is associated with lower use of maternal care services and may lead to worse maternal health outcomes. There is need for enhanced effort in addressing social and gender norms that perpetuate IPV, and this study can contribute to guiding policy interventions and community responses towards IPV.